Regional Innovation Strategies in a Cross-border Environment - Oto Hudec; Natasa Urbancikova (European Regional Science Association (ERSA), 2010)
Innovations are considered to discover new solutions to exploit novelty in the technological, but in social and economic fields as well. It means, the concept of innovations is true also for a sustainable development. The sustainability of the regional strategies is studied at the background of the regionalisation of the governance system. Particularly, the regions of Eastern Slovakia and Northern Hungary, both having a tradition of heavy industry, are studied in their cross-border innovation and sustainability context. The realization of the joined regional innovation strategy represents a unique opportunity to test and implement the RIS process in a cross-border environment. The main priority, renewable energy sources, results from the historical heavy industry path, the cross-border clusters and especially in. The path dependence concept is applied to two border regions is studied on the background of historical and economic transformation along the axes: - from centrally planned economy to market economy - from sectoral orientation of economy to regionalized economy - from industrial economy to knowledge-based economy and services - from environmentally harmful production to renewable energy sources sector - from vertical organization and administration to horizontal partnerships and clustering - from regional production to regional innovations - from national governance to multi-level and cross-border regional governance
Keywords: 330